DOP023 Tofacitinib for the treatment of ulcerative colitis: up to 4.4 years of safety data from global clinical trials. (16th January 2018) - Sandborn, W J; Panés, J; D'Haens, G R; Sands, B E; Su, C; Moscariello, M; Jones, T V; Pedersen, R D; Friedman, G S; Lawendy, N; Chan, G
Abstract: Background: Tofacitinib is an oral, small-molecule Janus kinase inhibitor that is being investigated for ulcerative colitis (UC). The safety and efficacy of tofacitinib for the treatment of moderate to severe UC was evaluated in OCTAVE induction and maintenance Phase (P) 3, randomised, placebo-controlled studies. 1 Long-term safety and efficacy of tofacitinib for UC are being evaluated in an ongoing, open-label, long-term extension (OLE) study. 2 We present an updated integrated analysis of the safety profile of tofacitinib observed during the UC global clinical development programme, with tofacitinib exposure up to 4.4 years. Methods: Patients who received placebo, tofacitinib 5 or 10 mg twice daily (BID) were analysed as three cohorts: induction (P2/P3 induction, n = 1220); maintenance (P3 maintenance, n = 592); and overall (patients receiving tofacitinib 5 or 10 mg BID in P2, P3, or the OLE study, n = 1157; 1613 patient-years [PY] of exposure). Data are shown as of December 2016. Proportions and incidence rates (IRs; patients with events per 100 PY) were evaluated for adverse events (AEs) of special interest. Opportunistic infections (OIs), malignancies, major adverse cardiovascular events (MACE), and gastrointestinal perforations (GIP) were reviewed by independent adjudication committees. Results: A total of 1157 patients received ≥1 dose of tofacitinib 5 or 10 mg BID with 1613 PY of tofacitinib exposure and up to 4.4 years of treatment. Demographics and disease characteristics were generally similar among the treatment groups in each cohort. In induction studies, AEs of special interest were similar for tofacitinib and placebo groups. In the maintenance cohort, IR of herpes zoster (HZ) was numerically higher with tofacitinib 5 mg BID (2.1) and significantly higher with tofacitinib 10 mg BID (6.6) vs. placebo (1.0). IRs for other AEs of interest were similar across treatment groups. For the Overall cohort, the majority of patients ( N = 971, 84%) received an average dose of tofacitinib 10 mg BID. IRs for AEs of special interest were: death, 0.2; serious infection, 2.0; OIs, 1.3; HZ, 4.1; malignancy (excl. non-melanoma skin cancer [NMSC]), 0.5; NMSC, 0.7; MACE, 0.2; and GIP, 0.2. Conclusions: Tofacitinib treatment in patients with UC was associated with dose-dependent risk of HZ. These results show an overall manageable safety profile of tofacitinib 5 and 10 mg BID in the UC programme, generally similar to that previously reported in the tofacitinib rheumatoid arthritis programme and to that of other UC therapies including biologics. References: 1. Sandborn WJ et al. Tofacitinib as induction and maintenance therapy for ulcerative colitis. N Engl J Med, 2017:376;1723–36. 2. Lichtenstein GR et al. Tofacitinib, an oral Janus kinase inhibitor, in the treatment of ulcerative colitis: open-label, long-term extension study. Am J Gastroenterol, 2017;112(S1). [Abstract 714].